Bioequivalence of a Liquid Formulation of Alpha1-Proteinase Inhibitor Compared with Prolastin®-C (Lyophilized Alpha1-PI) in Alpha1-Antitrypsin Deficiency - Barker, Alan F; Campos, Michael A; Brantly, Mark L; Stocks, James M; Sandhaus, Robert A; Lee, Douglas; Steinmann, Kimberly; Lin, Jiang; Sorrells, Susan (Chronic obstructive pulmonary disease, 2017)
This study evaluated the bioequivalence, safety, and immunogenicity of a new liquid formulation of human plasma-derived alpha 1 -proteinase inhibitor, Liquid Alpha 1 -PI, compared with the Lyophilized Alpha 1 -PI formulation (Prolastin®-C), for augmentation therapy in patients with alpha 1 -antitrypsin deficiency (AATD). In this double-blind, randomized, 20-week crossover study, 32 subjects with AATD were randomized to receive 8 weekly infusions of 60 mg/kg of Liquid Alpha 1 -PI or Lyophilized Alpha 1 -PI. Serial blood samples were drawn for 7 days after the last dose followed by 8 weeks of the alternative treatment. The primary endpoint was bioequivalence at steady state, as measured by area under the concentration versus time curve from 0 to 7 days (AUC 0-7 days ) postdose using an antigenic content assay. Bioequivalence was defined as 90% confidence interval (CI) for the ratio of the geometric least squares (LS) mean of AUC 0-7 days for both products within the limits of 0.80 and 1.25. Safety and immunogenicity were assessed. Mean alpha 1 -PI concentration versus time curves for both formulations were superimposable. Mean AUC 0-7 days was 20 320 versus 19 838 mg × h/dl for Liquid Alpha 1 -PI and Lyophilized Alpha 1 -PI, respectively. The LS mean ratio of AUC 0-7 days (90% CI) for Liquid Alpha 1 -PI versus Lyophilized Alpha 1 -PI was 1.05 (1.03-1.08), indicating bioequivalence. Liquid Alpha 1 -PI was well tolerated and adverse events were consistent with Lyophilized Alpha 1 -PI. Immunogenicity to either product was not detected. In conclusion, Liquid Alpha 1 -PI is bioequivalent to Lyophilized Alpha 1 -PI, with a similar safety profile. The liquid formulation would eliminate the need for reconstitution and shorten preparation time for patients receiving augmentation therapy for AATD.